Teacher’s Participation in Academic Administration at Khaosaming 1 Network School under Trat Primary Educational Service Area Office - มาศหิรัญ, สุณิษา; คงเที่ยง, สมศักดิ์; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were to 1) to study teacher’s participation in academic administration at Khaosaming 1 Network schools under Trat Primary Educational Service Area Office. 2) to compare teacher’s participation in academic administration classified by gender, education level and teaching experience. and 3) to explore guidelines for enhancing teacher’s participation in academic administration. The sample consisted of 108 teachers from Khaosaming 1 Network schools under Trat Primary Educational Service Area Office. The sample size was determined using Krejcie and Morgan's table (Krejcie & Morgan, 1970). The participants were selected using stratified random sampling, with individual schools serving as strata. The research instrument was a questionnaire with a reliability coefficient of 0.941. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, t-test, and F-test. In addition, semi-structured interviews were conducted to obtain guidelines for development, and qualitative data were analyzed using content analysis.           The results revealed that: 1. Overall, teachers’ participation in academic administration was at a high level. 2. Comparisons of teachers’ participation in academic administration classified by gender and educational level showed no statistically significant differences. However, when classified by work experience, statistically significant differences were found in the school curriculum development at the .05 level. 3. The guidelines for enhancing teachers’ participation in academic administration emphasized learner-centered instructional management, curriculum development aligned with the school context and learners’ needs, collaborative planning of diverse assessment approaches and utilization of assessment results to improve learners, promotion of participation and professional learning exchange among teachers, and the use of instructional media and digital technology to enhance the effectiveness and quality of educational management.